2020
DOI: 10.1038/s41598-020-73357-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of postoperative outcomes between patients with positive and negative straight leg raising tests who underwent full-endoscopic transforaminal lumbar discectomy

Abstract: Full-endoscopic transforaminal lumbar discectomy (FETD) is increasingly used in patients with lumbar disc herniation (LDH). There is little knowledge on the related factors, including the straight leg raising test (SLR), that influence the operation. Consecutive patients with LDH who came to our hospital from August 2015 to September 2016 and underwent FETD surgery were included. Four kinds of scores, including the VAS (lumbar/leg), ODI and JOA values, were measured and reassessed after FETD to assess the surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…At present, endoscopic surgery, a minimally invasive surgery technique, is considered to be an extension of alternative to spinal surgery (10). The surgical indications for endoscopic spine surgery are still increasing due to the release of practical and reliable clinical results (11,12). Spinal endoscopy is now used to treat not only disc herniation but also LSS (13).…”
Section: Introductionmentioning
confidence: 99%
“…At present, endoscopic surgery, a minimally invasive surgery technique, is considered to be an extension of alternative to spinal surgery (10). The surgical indications for endoscopic spine surgery are still increasing due to the release of practical and reliable clinical results (11,12). Spinal endoscopy is now used to treat not only disc herniation but also LSS (13).…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic of sciatic herpes zoster is the absence of LBP. In LDH, the patient often complains LBP to some degree (8). It was reported that LBP in LDH may be caused by multiple factors such as discogenic LBP, radicular LBP that is relieved by nerve root decompression, and the LBP due to endplate degeneration (9).…”
Section: Discussionmentioning
confidence: 99%
“…LDH is one of the most common disorders, with a prevalence of approximately 77.8% among adults [19].…”
Section: Introductionmentioning
confidence: 99%